PENENTUAN INDEKS KESUBURAN TANAH PADA BEBERAPA PENGGUNAAN LAHAN DI SUB DAS JENELATA, KABUPATEN GOWA - Aqidah, Nur; Ibrahim, Bakhtiar; Saida, Saida (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
The absence of data regarding soil fertility within a watershed leads to the selection of land use that does not align with the appropriate level of land capability and suitability. The objective of this study is to assess the soil fertility index in different land uses within the Jenelata sub-watershed and identify the land map unit with the highest soil fertility. The study was conducted from February 2024 until May 2024. The study is a soil survey investigation that has been validated by laboratory analysis. The survey area comprises 23 Land Map Units (SPL) derived from the integration of soil type maps, slope maps, and land use maps. Each SPL is represented by three composite soil samples, corresponding to each land use category. Soil sampling was conducted at a depth of 0-30 cm. The observed characteristics include Cation Exchange Capacity (CEC), Organic Carbon (C-Organic), total Nitrogen (N), accessible Phosphorus (P), exchangeable Potassium (K), exchangeable Magnesium (Mg), exchangeable Calcium (Ca), and exchangeable Aluminum (Al). The soil analysis data are utilized to evaluate the soil fertility index. The study revealed that the soil fertility index value in the Jenelata sub-watershed ranged from 195 to 215, indicating a moderate to relatively high level. The maximum soil fertility index value of 215 was seen in the utilization of secondary dryland forest land.